2019
DOI: 10.1039/c9an01456j
|View full text |Cite
|
Sign up to set email alerts
|

Tunicamycin induced endoplasmic reticulum changes in endothelial cells investigated in vitro by confocal Raman imaging

Abstract: This paper describes how tunicamycin (Tu), the most widely used pharmacological agent for inducing endoplasmic reticulum (ER) stress, interacts with endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Lipid profiling using 1 H nuclear magnetic resonance (NMR) showed that protein misfolding caused by acyclic retinoid significantly reduced unsaturated FA content in a human cancer cell line [120]. Imaging by scanning electron microscopy and Raman spectroscopy of individual, tunicamycin-treated endothelial cells showed a decrease in ER phospholipid content [121]. Furthermore, mass-spectrometry-based lipid analysis showed that a short cultivation of S. cerevisiae in DTT is sufficient to induce substantial lipidomic changes, including an increase in overall PA and a shift of PA lipids toward a higher average acyl chain length and a greater unsaturation [122].…”
Section: Crosstalk Between Proteotoxicity-and Lipotoxicity-induced Upr-ermentioning
confidence: 99%
“…Lipid profiling using 1 H nuclear magnetic resonance (NMR) showed that protein misfolding caused by acyclic retinoid significantly reduced unsaturated FA content in a human cancer cell line [120]. Imaging by scanning electron microscopy and Raman spectroscopy of individual, tunicamycin-treated endothelial cells showed a decrease in ER phospholipid content [121]. Furthermore, mass-spectrometry-based lipid analysis showed that a short cultivation of S. cerevisiae in DTT is sufficient to induce substantial lipidomic changes, including an increase in overall PA and a shift of PA lipids toward a higher average acyl chain length and a greater unsaturation [122].…”
Section: Crosstalk Between Proteotoxicity-and Lipotoxicity-induced Upr-ermentioning
confidence: 99%
“…The intensities of the relevant Raman bands at 2840−2870, 1073, 1549, 1086, and 785 cm −1 were analyzed to determine the distribution positions of the components in the cells (Figure 3A). These bands were attributed to the CH 2 stretching of the lipid, the C−N stretching vibration of the lysosome (Lys), 35 the C−C stretching of the mitochondria (Mit), 35 and the PO 2 − stretching of the phospholipids, respecting the endoplasmic reticulum (ER) membrane, 36 and the O−P−O stretching of the DNA. 34 The center of the cells and the band at 1001 cm −1 of phenylalanine (yellow) were occupied by the cell nucleus (purple).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The shift of vascular function to vasoconstriction, proinflammatory state, oxidative stress and NO deficiency may lead to endothelial dysfunction and injury. This shift is a key event in the pathophysiological process of cardiovascular diseases, including hypertension, diabetes, atherosclerosis, arterial hypertension and pulmonary hypertension ( 28 , 29 ). In the present study, HUVECs were treated with 1 µM AngII for 24 h to establish an AngII-induced endothelial cell model.…”
Section: Discussionmentioning
confidence: 99%